The “outsourcing” and management consulting in a dimensional systemic model - António, N. (2012)
In an era of particularly intense competition, the consulting services are becoming an increasingly important source of aid for strategic making and an important way to increase efficiency and quality in the various business activities. Many managers consider the consulting services as an influential and powerful tool for organizational change, bringing new life to the organization. The purpose of this article is to study this situation. We will carry out a study in one of the biggest Portuguese private bank, in order to show the real value of management consultancy when it combines, a broad view of business, to study a set of skills closely linked to the relationship between service and market, and when it is focusing on "core" competencies, resources and offers increasingly facilitating the well being of the client, that is, showing how a company can foster creativity and dynamism in the activities of companies when operated through the potentials of TIG (information technology management).